PERANAN ORANG KRISTEN DALAM PUSARAN POLITIK DI INDONESIA (Suatu Tinjauan Historis -Teologis) - Samuel Benyamin Hakh (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2019)
This paper is prepared to explain that the struggle for Indonesian independence was carried out for centuries by all people in Indonesia, including Christians, with sweat and tears, even with bloodshed. Therefore, Indonesian independence is not a gift or effort from a particular group, but it is a gift from God which is expressed through the struggle of all groups and tribes throughout Indonesia from Sabang to Merauke and from Sangir to Rote. So, as a nation that is dignified, and who upholds justice and truth, we must be honest with the history of our own nation. With that, the independence of Indonesia as a gift from God, we should be accepted with thanksgiving while we are together to build a just, prosperous, peaceful of Indonesia in the future.